Limited plasticity of anatomical and hydraulic traits in aspen trees under elevated CO2 and seasonal drought. Issue 1 (29th October 2021) - Lauriks, Fran; Salomón, Roberto Luis; De Roo, Linus; Goossens, Willem; Leroux, Olivier; Steppe, Kathy
Abstract: The timing of abiotic stress elicitors on wood formation largely affects xylem traits that determine xylem efficiency and vulnerability. Nonetheless, seasonal variability of elevated CO2 (eCO2 ) effects on tree functioning under drought remains largely unknown. To address this knowledge gap, 1-year-old aspen ( Populus tremula L.) trees were grown under ambient (±445 ppm) and elevated (±700 ppm) CO2 and exposed to an early (spring/summer 2019) or late (summer/autumn 2018) season drought event. Stomatal conductance and stem shrinkage were monitored in vivo as xylem water potential decreased. Additional trees were harvested for characterization of wood anatomical traits and to determine vulnerability and desorption curves via bench dehydration. The abundance of narrow vessels decreased under eCO2 only during the early season. At this time, xylem vulnerability to embolism formation and hydraulic capacitance during severe drought increased under eCO2 . Contrastingly, stomatal closure was delayed during the late season, while hydraulic vulnerability and capacitance remained unaffected under eCO2 . Independently of the CO2 treatment, elastic, and inelastic water pools depleted simultaneously after 50% of complete stomatal closure. Our results suggest that the effect of eCO2 on drought physiology and wood traits are small and variable during the growing season and question a sequential capacitive water release from elastic and inelastic pools as drought proceeds. Abstract : Elevated CO2 has limited season-dependent effects on anatomical and hydraulic traits of aspen trees with increased xylem vulnerability to embolism occurring during early but not late season drought.